Implementation of multicarrier PWM based 7-level Z-source cascaded H-bridge inverter - Palanisamy Ramasamy; Vidyasagar Sugavanam; Kalyanasundaram Vakesan; Subbulakshmy Ramamurthi; Selvakumar Kuppusamy; Usha Sengamalai; Thamizh Thentral (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper elucidates the realization of multicarrier pulse width modulation (MC-PWM) based 7-level Z-source cascaded H-bridge inverter. MC-PWM technique is developed to generate switching pulses for Z-source inverter; it leads to boost the inverter output voltage with help of shoot through mode of operation. The output of Z-source inverter is connected to 7-level cascaded H-bridge inverter. Cascaded H-bridge inverter system much suitable for AC load drive, high voltage and high power and industrial applications. This proposed system provides reduced total harmonic distortion, improved stepped output voltage and current, nearly sinusoidal output voltage and reduced voltage stress across the switching devices. The inductors and capacitors values are selected based on the boosting level of Z-source inverter. The simulation results of proposed 7-level Z-source cascaded H-bridge inverter with MC-PWM technique is verified using MATLAB/Simulink.